Candidacy Endorsement and Rebuttals as Mediated Campaign Strategies in The 2023 Nigerian Election - Fredrick Friday John; Olubimpe Olasunmbo Adekunle (RIRAI Publisher, 2024)
Endorsements trigger arguments and rebuttals about the relevance of political actors by the spokesmen frontline political parties. Previous linguistic studies have focused more on campaign speeches; little attention has been paid to endorsement as a campaign strategy. This study investigated the endorsement speech of Olusegun Obasanjo (OBJ) and rebuttals by supporting and opposing spokesmen of Labour Party (LP), People’s Democratic Party (PDP), and All Progressive Congress (APC) in Nigerian elections, identifying and analysing the locutionary, illocutionary and Pragmatic strategies. The qualitative design was used. Data comprise purposely selected and transcribed texts from Channels Television (CHNLSTV) interview, moderated by Seun Okinbaloye. Data was downloaded from their YouTube channel Mariana Sbisa’s Speech Act, supported by John Searle’s classification of illocutionary, and the textual part of Mey’s Pragmatic Acts were used as the framework. The locutionary strategies of endorsements and rebuttals in the data were: juxtaposition with alternative facts, conscious denial of position and facts, affirmation of thoughts, representation of opinionated position and counter-position, acceptance of position or facts and attack/defense of personality traits. Three major illocutionary acts: expressive, representative, and directive, were seen. Pragmatic resources such as inference, reference, relevance, metaphor and shared situational knowledge underlined. Expressive was achieved by condoning, criticising, condemning and praising. Representative was constructed by the forces of asserting, accusing, comparing and contrasting or juxtaposing. Directive was justified by defining, declaring, endorsing and analogising. The study concludes that endorsements and rebuttals are the performance ratings of political agents.